Zinc-Deprivation, Motor Activity and Attention - J Gordon Millichap (Pediatric Neurology Briefs)
The effects of moderate dietary zinc deprivation (2 mcg/gm diet) compared to an adequate zinc intake (50 mcg/gm) were compared using 24-hour activity patterns and an attention task performance in 10 adolescent female monkeys (18-33 months of age) at the California Regional Primate Research Center, University of California, Davis, CA.